The Effect of Liberalization on Export-Import in Indonesia - Sofjan, Muhammad (International Journal of Economics and Financial Issues, 2017)
This study investigates how international trade are affected by liberalization, starting with the export and import function. It aims to determine the main empirical factors of imports and exports in Indonesia, which is one of the developing countries that are participating in cooperation agreements for free trade. Import and export functions are then added to the liberalization factors to determine the impact of liberalization on export and import activities in Indonesia in both the short and long terms. We find that world income, relative price, and export taxes affect the volume of exports in the long term, while import volume is affected by relative price, domestic income, and import duties in the long term. Thus, a long-term equilibrium relationship can be established between the variables for research purposes. Liberalization policies have a positive and significant impact on imports in the short term. Keywords: Liberalization, Export, Import, World Income, Relative Price JEL Classifications: F15, F62, G13